(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
To solve the stress shielding problem in the orthopaedic implants applications, lightweight lattice structures were designed to optimize the internal of the implants. The variation of truss size of lattices can affect the mechanical performances of implants. Also the printed dimension of the shell is closely related to the fitting of implants, and its thickness will again affect the mechanical property of the printed implants. In this study, high resolution X-ray computed tomography was used to quantitatively investigate the consistency of the dimensions in the designed and printed orthopaedic implants.